Residual velocity for the truncated ogival-nose projectile into stiffened plates. (17th August 2016) - Zhan, Tingbian; Li, Jinzhu; Lv, Shufang; Chen, Zhigang
Abstract : Residual velocity of the projectile plays an importance role in evaluating the resistance of the target. A mathematical model of the truncated ogival-nose projectile penetrating into the stiffened plates is designed to describe the destruction according to the momentum conservation theorem, and relationships between the residual velocity and penetration locations of stiffened plates are obtained during penetrating. The destruction forms of stiffened plates include slug and petal, which contain a base plate, transverse stiffeners and longitudinal stiffeners. By analysing the model, we obtained that the momenta on the petal are much greater than those of the slug, and the petal momentum of the stiffener is much greater than that of the base plate. When the petal momentum of the stiffener reaches the maximum, the displacement of the projectile is only related to its own shape. As the truncation circle is tangent to the axis of the stiffener, the velocity loss of the projectile consumed by the stiffener reaches the maximum. A series of experiments is carried out to explore the impact characteristics of stiffened plates struck by the ogival-nose projectile, whose initial velocities range from 546 to 618 m/s. Residual velocities of nine different locations are measured, and the data are in good agreement with the calculation results of the model.